Pembelajaran Tari Siwar Menggunakan Metode Drill pada Kegiatan Ekstrakurikuler di Mts Negeri 1 Lahat - Putri, Helen Dwi; Wardiah, Dessy; Nurdin, Nurdin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Education cannot be separated from the teaching and learning process between teachers and students in a school institution, which plays an active role in providing education to students. This research if focused on extracurricular activities in school, Lahat district itself not only has a lot of diversity in dance, but also includes an area dubbed the student city because of the many schools that were established there, so the researchers chose to develop the art of dance, one of which is the Siwar dance throught extracurricular activities at school. Therefore, of couse, there are difficulties that often arise inlearning the siwar dance in extracurriculler activities, including students finding it difficult to understand the movements when demonstrastrating the dance using the siwar directly,because it takes strong concentration to establish the siwar on the fingers.With this the writer aimed to describe about Siwar Dance Lesson on Extracurricular Activity in MTS Negeri 1 Lahat by using Drill method. With qualitativedescriptive as the research method and withobservation,interviewsalso documentation as collectingdata. The result shown that the extracurricular activity in MTS Negeri 1 Lahat run well so it created achievements and becoming the sample for another extracurricular activity. The benefit of this research is to share the knowladge especially in educationand as references for the next researcher.